Comparison of implicit and explicit preference toward multiple colour combinations. (2018) - Muramatsu, Keiichi; Fang, Siyuan; Kaede, Kazunori; Tanaka, Eiichiro; Watanuki, Keiichi; Matsui, Tatsunori
Emotional responses to colour stimuli are referred to as colour emotions, and their psychological constructs relating to colour attributes have been discussed in past studies. However, colour preference, one type of colour emotions, has yet to be explained due to cultural and sex differences. In the current study, we investigated an implicit attitude towards multi-colour stimuli, which was regarded as a colour emotion judged by unconscious mental processes. To extract the implicit attitude and compare it with the explicit one, we conducted affect misattribution procedure, a method of measuring attitudes in social psychology. We obtained emotional responses different from ones measured using semantic differential method in a previous study. We analysed the characteristics of the multi-colour stimuli using scores in computed by the affect misattribution procedure. Results revealed that the explicit attitude towards multi-colour stimuli was affected by their chroma and hue values. The current study provided fundamental knowledge to clarify the psychological construct of colour preference.